IMPLEMENTASI PENDEKATAN ETNOMATEMATIKA PADA MATERI GEOMETRI UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA KELAS IV SDIT RAUDHATUR RAHMAH PEKANBARU - Rinda Riani Putri; Jesi Alexander Alim; Muhammad Fendrik Muhammad Fendrik (STKIP Subang, 2026)
This study was motivated by the low numeracy skills of elementary school students in geometry learning and the abstract nature of mathematics instruction that is rarely connected to students’ culture and daily lives. The study aimed to determine the effect of implementing an ethnomathematics approach in geometry learning on the numeracy skills of fourth-grade students at SDIT Raudhatur Rahmah Pekanbaru. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of two classes, namely an experimental class and a control class, each consisting of 25 students. Data were collected through pretest and posttest instruments as well as documentation. The data were analyzed using descriptive statistics, normality tests, the Mann–Whitney U test, and N-Gain analysis. The results showed that the average posttest score of the experimental class was 88.72, which was higher than the control class score of 59.96. The Mann–Whitney U test result obtained an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the two classes. The N-Gain analysis also revealed that the improvement in students’ numeracy skills in the experimental class reached 58.99% in the moderate category, while the control class only reached 3.82% in the low category. Therefore, the implementation of the ethnomathematics approach in geometry learning significantly affected the improvement of elementary school students’ numeracy skills. The ethnomathematics approach was proven to create more contextual, active, and meaningful learning through the integration of local culture into mathematics instruction.